Effect of exposure factors on radiographic image quality in the use of abdominal phantom with ap projection - Nanik Suraningsih; Aryadiva Nugrahaning Prayoga; Novita Alfiani (Science Midwifery, 2023)
Radiographic examination of the anatomy of the body can provide the maximum possible information that is easily determined by the Radiologist, if the quality of the radiographic image is good. To be able to produce radiographs that provide maximum information, optimal radiography is needed. In radiographic examinations, factors are needed that can affect the quality of photos in order to get better results. These factors include the exposure factor. The exposure factor consists of voltage (Kv), tube current (mA) and time (s). The purpose of the study was to determine the exposure factor on the quality of radiographic images on the use of abdominal phantoms with AP projections. The method used was experimental research. In some variations of the expulsion factor, there is no difference in quality both in terms of contrast and sharpness. The images produced from each variation are good and informative, so it can be assumed that the use of the exposure factor is chosen the most minimal so that the exposure or dose received is smaller. Image quality analysis should be made with a wider range of Kv and mAs, and using phantom objects other than abdominal phantoms.